Commentary: Lingering questions about the Social Responsiveness Scale short form. A commentary on Sturm et al. (2017). (September 2017) - Kaat, Aaron J.; Farmer, Cristan
Abstract : Read the full article at doi: 10.1111/jcpp.12731